Biotic resistance affects growth and reproduction, but not survival of a high‐impact woody invader in African savannas. (30th April 2018) - te Beest, Mariska; Mpandza, Nokukhanya J.; Olff, Han
Abstract: Question: Biotic resistance is defined as the reduction in invasion success caused by the native community through competition, herbivory and/or pathogens. Biotic resistance has mostly been studied during the initial stages of invasion. However, to what extent biotic resistance hampers survival, or persistence, of invaders in the longer term is often not known. We studied how native grassland communities affected growth, reproduction and survival during the adult life stage of the high‐impact woody invader Chromolaena odorata under different water availability treatments. Location: Hluhluwe‐iMfolozi Park, South Africa. Methods: We performed a 2‐years full‐factorial field experiment in a savanna grassland where we manipulated water availability and neighbouring vegetation; in one‐third of the plots vegetation was cleared and planted with C. odorata monocultures, in one‐third C. odorata shrubs were planted in grasslands, and one‐third were unplanted grassland controls. Results: Growth and reproduction of adult C. odorata were greatly reduced due to competition with native grasses, but not survival of C. odorata . Shrub survival was high and did not differ in plots with and without grass. Water availability did not affect growth, reproduction and competitive ability of C. odorata, but higher water availability did increase the competitive ability of the grasses. Soil moisture levels were lower in grasslands planted with C. odorata compared to unplanted controls, independent of the water treatment, suggesting higher water use of C. odorata compared to native grasses. Conclusions: Savanna grasslands have a strong competitive effect on invasion by the exotic woody shrub C. odorata, reducing growth and reproduction, but not survival of the shrub. We found no evidence that biotic resistance was stronger under more unfavourable abiotic conditions, as C. odorata was equally impacted in all water treatments. The high survival rates of C. odorata suggest that competitive interactions are not likely to prevent invader persistence in the landscape. Invader persistence is important in determining longer‐term invasion success as well as invader impact, and the concept of persistence should not be overlooked in studies on invasive species. Abstract : We studied the biotic resistance of savanna grasslands to the high‐impact woody invader Chromolaena odorata under different water treatments. Competition with native grassland communities strongly reduced growth and reproduction, but not survival of adult C. odorata plants across all water treatments. This suggests that competitive interactions may slow down the invasion of C. odorata but unlikely prevent its persistence in the landscape.